Gender differences in D2 dopamine receptor binding in drug-naive patients with schizophrenia: an [123I]iodobenzamide single photon emission computed tomography study - Schröder, Johannes; Bubeck, Bernd; Fauth Silvestri, Simone; Demisch, Sibylle; Sauer, Heinrich (Psychiatry research, 1997)
Recent studies have described a left lateralized striatal asymmetry of D2 dopamine receptors in male patients with schizophrenia. To replicate this finding and to explore its potential functional consequences, we investigated the D2 dopamine receptor system in 23 drug-naive patients with schizophrenia using single photon emission computed tomography (SPELT). Patients were examined in the drug-naive state and 72 h after completing a standardized neuroleptic treatment with benperidol (12-16 mg/day) for 25 days. Each SPELT examination comprised two scans: the first scan was taken 2 h after intravenous injection of 185 MBq [123I]iodobenzamide. After completion of the first scan, patients received benperidol (8 mg) intravenously. The second scan was started 20 min later. For analysis, basal ganglia to frontal cortex ratios were calculated. Fifteen of the 23 patients originally recruited completed the study on day 28. When compared to female patients, male patients showed a left lateralized asymmetry of striatal D2 dopamine receptor binding in the drug-naive state with an almost significant (P = 0.07) sex X hemisphere interaction. In the male patients, benperidol challenge led to a reversal of asymmetry patterns. These findings support previous reports of a left lateralized striatal D2 receptor binding in drug-naive male patients with schizophrenia and suggest that this asymmetry may affect the binding of conventional neuroleptics such as benperidol at the D2 dopamine receptor.